With the Fifth Army Air Force photos from the Pacific Theater - Gallagher, James P. (Johns Hopkins University Press, 2001)
James P. Gallagher saw action in the Southwest Pacific Theater during World War II. This collection of his photographs shows the life of the US airmen, from the poor living conditions and their routine activities to the raw experience of war.
Includes index.
Keywords: Gallagher, James P. <1920->; United States - Army Air Force - Air Force, 5th - Biography; United States - Army Air Force - Air Force, 5th - Pictorial works; United States. -- Army Air Forces -- Biography; United States. -- Army Air Forces. -- Air Force, 5th -- Pictorial works; USA -- Army -- 5; Weltkrieg (1939-1945); World War, 1939-1945 -- Personal narratives, American; World War, 1939-1945 -- Campaigns -- Japan -- Pictorial works; World War, 1939-1945 -- Campaigns -- Pacific Ocean -- Pictorial works; World War, 1939-1945 -- Photography; Pazifikkrieg -- 1941-1945; Luftwaffe; USA; Bildband; Biografie